Strategi Komunikasi Dinas Sosial Kota Medan dalam Upaya Pemberdayaan Ekonomi Masyarakat - Aulia, Ananda Rizky; Tamrinsikumbang, Ahmad; Muktarruddin, Muktarruddin (AHKAM, 2023)
The aim of this research is to determine the communication strategy of the Medan City Social Service in empowering the community's economy. This research used a qualitative approach with descriptive methods, the informants for this research were 6 people who were determined purposively. The data collection techniques used were observation, interviews and documentation. The results of the first research regarding the economic conditions of the people in Medan City are that the Medan City Social Service in 2022 will experience growth of 4.71 percent. From the production side, the three categories of business fields that gave the highest growth were the transportation and warehousing business fields which experienced the highest growth of 11.67 percent. And in terms of expenditure, three components with capital formation such as household consumption expenditure amounted to 4.78 percent. The second is related to the communication strategy of the Medan city social service in an effort to empower the community's economy. by providing skills training for poor families to 100 people with funding allocated from the Medan city APBD. Providing KUBE assistance every year to organizations or MSMEs means providing assistance to the community and monitoring the development of businesses that have been assisted. Through communication carried out by the Social Service, changes and progress have occurred in the economic empowerment of the people of Medan City. This communication strategy plays an important role in ensuring that the businesses that have been assisted run well and develop. The strategic steps for the Medan city social service that must be implemented include program planning, implementing the preparation of policy materials, organizing the handling of the family hope program, preparing guidance for social potential and social welfare which operates in the field of social welfare, implementing the preparation of policy materials for standard operating procedures.